Emergent Readers and the Joy of Reading: A Finnish Perspective - Juli-Anna Aerila; Tuula Merisuo-Storm (Scientific Research Publishing, 2022)
Good reading skills are an essential part of everyday life. This article presents two Finnish projects JEKKU (2010-2011) and LUKUINTO (2012-2015) that aim to enhance children’s engagement and success in reading. The research results of these studies are described in this article from three perspectives: reading skills, reading materials, and reading interventions. The main aim of this article is to highlight how helping children to read and enjoy reading is not complicated. Our studies show that children who are interested in what they read, and experience pleasure and success while reading, are provided with comfortable reading places and enough time to concentrate on reading, read more and become confident readers. The basics of reading skills and the attitudes towards reading are created in the early years, so it is important to concentrate on making these reading experiences more interesting and enjoyable for all young children. This article is not a traditional research article, but collects the results of the two projects together and strives to give concrete tools for reading enhancement to all educators.